Rapid, stable and self-powered perovskite detectors via a fast chemical vapor deposition process. Issue 30 (27th March 2017) - Tong, Guoqing; Geng, Xiangshun; Yu, Yongqiang; Yu, Linwei; Xu, Jun; Jiang, Yang; Sheng, Yun; Shi, Yi; Chen, Kunji
Abstract : Organometal halide perovskite materials are outstanding candidates not only for solar cells but also for photo-detection. Abstract : Organometal halide perovskite materials are outstanding candidates not only for solar cells but also for photo-detection. In this work, we develop a well-controlled lower temperature (<120 °C) and fast chemical vapor deposition process (LFCVD) to fabricate photovoltaic detectors with a high speed response ( τ rise / τ fall ∼ 460 ns/940 ns) and a 3 dB-bandwidth above 0.9 MHz, which are the highest among those with a large active area (>0.1 cm 2 ) without external power supply. Remarkably, the perovskite photovoltaic detectors demonstrate an excellent air-exposure stability for more than two months without particular encapsulation. These excellent performances are attributed to a well-controlled expansive gas–solid reaction and formation of perovskite crystallites that collide and pinch off the pinhole leakage paths at the grain boundaries. More importantly, the accumulated strain at the colliding grain boundaries leads to a selective evaporation of MAI during post-growth annealing, and thus passivate the local defects by the remnant PbI2 layer. These results highlight the potential of LFCVD perovskite materials in developing ultra-fast and self-driven photovoltaic detectors with outstanding stability and scalability.